IMPLEMENTASI SISTEM INFORMASI PEMBERKASAN ARSIP DENGAN MENGGUNAKAN METODE ALFABETIS KOMBINASI KLASIFIKASI PADA PT BPR MITRA CATUR MANDIRI MALANG - Lindawati, Lina; Suaedi, Daeng Ahmad; Widayanti, Rahayu (DINAMIKA DOTCOM, 2016)
PR PT Catur Mitra Mandiri is one of the financial institutions that provide services in operationsince 1993 has opened the cash office units that are in Turen, Kasembon, and Sumber pucungMalang. File storage customer is still done manually by filling division causing problems in theliquefaction process the file because the file received from the cash office between 3 to 4 days. Inthis case the division filling require a computerized system that can be used for filing process so asto help the division filling.The purpose of this research is the establishment of archival filing application by using thealphabetical and classified in PT BPR standalone chess partner. The method used is a method inwhich the alphabetical filing credit files are archived alphabetically taken from the name of thecustomer, while the common files are grouped by their method of classification that incoming filesare grouped by file type. Data collection methods used were interviews and surveys. Systemdevelopment method used is SDLC Waterfall. The system that has been built providing informationon the ease of file bermafaat for filling division and the companys employees. These systems canspeed up the process of filing in an Independent Catur Mitra PT BPR. Can help improve theperformance of officers filling. And simplify the process of printing daily or monthly report onBPR PT Catur Mitra Mandiri.Keywords: System Information, Archives, Methods, Alphabetical, Classification